ENHANCING ESSENTIAL OIL YIELD: UTILIZING INTERNAL CHOPPER IN STEAM DISTILLATION - I Made Rajendra; Ida Ayu Anom Arsani; I Made Sudana; I Gede Nyoman Suta Waisnawa (Logic : Jurnal Rancang Bangun dan Teknologi, 2024)
The objective of this study is to validate a novel method for chopping essential raw materials. To achieve this, we employed a distillation reactor equipped with an internal chopping module to enhance both the quantity and quality of Champaca essential oil production. Our experiments involved three variations of pre-distillation treatment: no chopping, chopping inside the reactor, and chopping outside the reactor. The distilled oil was subsequently analyzed using GC-MS. These three chopping methods resulted in varying amounts of linalool compounds. Unchopped essential materials yielded 6.54% linalool compounds, while internal chopping produced 32.33%, and external chopping resulted in 7.40% linalool compounds. The internal chopping method proved to be the most effective in increasing linalool compound content. Consequently, we can conclude that chopping materials within the distillation reactor during the steam distillation process significantly enhances the main compound's content.